2021
DOI: 10.1111/cas.14800
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term cultured autologous peripheral blood mononuclear cells as a potential immunogen to activate Tax‐specific CTL response in adult T‐cell leukemia patients

Abstract: Activation of CD8+ Tax‐specific CTL is a new therapeutic concept for adult T‐cell leukemia (ATL) caused by HTLV‐1. A recent clinical study of the dendritic cell vaccine pulsed with Tax peptides corresponding to CTL epitopes showed promising outcomes in ATL patients possessing limited human leukocyte antigen (HLA) alleles. In this study, we aimed to develop another immunotherapy to activate Tax‐specific CTL without HLA limitation by using patients’ own HTLV‐1‐infected cells as a vaccine. To examine the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The use of ATLL patients own peripheral blood mononuclear cells (PBMC) were also suggested to have an immunogen activity against the virus through activating Tax- specific CTLs [ 46 ]. Expressing Tax antigen, IL-12, and other stimulatory molecules in a cultured environment with the presence of both HTLV-1 infected cells and the patients' PBMC leads to CD8 + Tax-specific CTL responses.…”
Section: Resultsmentioning
confidence: 99%
“…The use of ATLL patients own peripheral blood mononuclear cells (PBMC) were also suggested to have an immunogen activity against the virus through activating Tax- specific CTLs [ 46 ]. Expressing Tax antigen, IL-12, and other stimulatory molecules in a cultured environment with the presence of both HTLV-1 infected cells and the patients' PBMC leads to CD8 + Tax-specific CTL responses.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that HTLV-1-infected cells are immunogenic because Tax functions to promote DC maturation in vitro [ 48 50 ]. Our previous study indicated that antigen-presenting cells co-cultured with short-term-cultured and MMC-treated PBMCs from ATL patients expressing HTLV-1 antigens were able to cross present Tax antigen and sensitize CD8 + CTLs [ 26 ]. In the present study, we demonstrated that vaccination with short-term-cultured autologous PBMCs actually induced a CD8 + CTL response in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that although HTLV-1 antigens are undetectable in the PBMCs from HTLV-1-infected individuals, they can be rapidly induced following in vitro culture [ 24 , 25 ]. Our recent study indicated that short-term-cultured PBMCs of ATL patients had the potential to activate antigen-presenting cells, allowing Tax antigen cross-presentation, co-stimulatory molecule expression, and IL-12 production, all of which are required to evoke CD8 + HTLV-1-specific CTLs [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CD160 35 and SLAMF7, 36 which are natural killer cell-mediated immunity, and CX3CR1 37 and ITGA4, 38 which are important factors for the control of tumour growth, were also impaired in the earlydeath group with an aggressive status. The recent clinical trial of a dendritic cell vaccine targeting Tax might be a promising strategy against ATL 39,40 and these immune strategies including adoptive T-cell therapies would be expected to induce functional Tax-specific CTLs. 4,6,41,42 Taken together, the strategy of Tax-targeting T-cell therapy would better be indicated only for ATL patients with Tax expression.…”
Section: Adam28mentioning
confidence: 99%